ANALISIS KEBUTUHAN AIR BERSIH PDAM KOTA PAYAKUMBUH TAHUN 2021-2040 KECAMATAN PAYAKUMBUH TIMUR (STUDI KASUS PDAM KOTA PAYAKUMBUH) - Nofrizal Nofrizal; Randi Triadhi (Ensiklopedia of Journal, 2023)
Rapid population growth makes all needs increase, one of which is the need for clean water. Clean water is the main source for human life, because all activities require clean water, such as bathing, drinking, washing and others. Seeing that every year the population of Payakumbuh City continues to increase so that this affects the amount of clean water to meet the needs of the population every year. This final project discusses analyzing PDAM clean water needs in Payakumbuh City, subdistrict  East Payakumbuh in 2021 to 2040. The purpose of this final project is to determine the need for clean water in Payakumbuh City based on an increase in population in the next 20 years. The research methods used to carry out this research include field observations, literate studies, interviews and data collection to relevant agencies and analysis of data processing. Based on the analysis, the average water demand in 2025 is 65.507 liters/second, in 2030 it is 74.126 liters/second, in 2035 it is 80.704 liters/second and in 2040 it is 87.854 liters/second. Thus, by knowing the increase in population in the next 20 years, it can be seen how much the average water demand for PDAM Kota Payakumbuh Kec. East Payakumbuh is needed in the next 20 years to meet the needs of the population, so it can be concluded that Payakumbuh City PDAM must increase the clean water discharge every year.Keywords: Raw water discharge, and usage discharge